Some New Evidence About the Effects of U.S. Antidumping Orders and Their Administrative Reviews on the Prices of Covered Import - William Nye (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2012)
U.S. antidumping duties are subject to administrative review—in which posted duties may be revised and final duties are determined. Reviews may occur annually for the life of the antidumping order. The level of antidumping duties is important not only as an index of the level of U.S. import protection, but for the inference these duties allow about the prices of the covered imports in the U.S. The present paper presents evidence from a sample of U.S. antidumping orders that are followed through as many as 15 administrative reviews. This evidence shows that the average level of final duties tends to decline over the course of successive reviews—suggesting a rise in U.S. price of covered imports, a result consistent with the predictions of both advocates and opponents of antidumping enforcement. Interestingly, the decline in average antidumping duties over successive reviews is entirely the result of firms with higher dumping duties disappearing from the review process (probably ceasing sales in the U.S.). For given firms surviving to be named in the next review, the antidumping duty increases from one review to the next. The paper is the first to report direct information about the unit value of covered imports contained in administrative review reports of the United States International Trade Commission. This fragmentary direct information about import price also suggests an increase in the price of covered imports over time. The paper is also the first to present information about the large number of firms—more than one third of those ever assigned a firm-specific duty– that are named in administrative reviews, but not in original antidumping orders.
Keywords: 330